A depositional model for deep‐lacustrine, partially confined, turbidite fans: Early Cretaceous, North Falkland Basin. Issue 1 (29th June 2018) - Dodd, Thomas J. H.; McCarthy, Dave J.; Richards, Philip C.
Abstract: This paper presents a model of facies distribution within a set of early Cretaceous, deep‐lacustrine, partially confined turbidite fans (Sea Lion Fan, Sea Lion North Fan and Otter Fan) in the North Falkland Basin, South Atlantic. As a whole, ancient deep‐lacustrine turbidite systems are under‐represented in the literature when compared with those documented in marine basins. Lacustrine turbidite systems can form extensive, good quality hydrocarbon reservoirs, making the understanding of such systems crucial to exploration within lacustrine basins. An integrated analysis of seismic cross‐sections, seismic amplitude extraction maps and 455 m of core has enabled the identification of a series of turbidite fans. The deposits of these fans have been separated into lobe axis, lobe fringe and lobe distal fringe settings. Seismic architectures, observed in the seismic amplitude extraction maps, are interpreted to represent geologically associated heterogeneities, including: feeder systems, terminal mouth lobes, flow deflection, sinuous lobe axis deposits, flow constriction and stranded lobe fringe areas. When found in combination, these architectures suggest 'partial confinement' of a system, something that appears to be a key feature in the lacustrine turbidite setting of the North Falkland Basin. Partial confinement of a system occurs when depositionally generated topography controls the flow‐pathway and deposition of subsequent turbidite fan deposits. The term 'partial confinement' provides an expression for categorising a system whose depositional boundaries are unconfined by the margins of the basin, yet exhibit evidence of internal confinement, primarily controlled by depositional topography. Understanding the controls that dictate partial confinement; and the resultant distribution of sand‐prone facies within deep‐lacustrine turbidite fans, is important, particularly considering their recent rise as hydrocarbon reservoirs in rift and failed‐rift settings.